Le système de dénomination Balant - Mansaly, Jules (AAeO - Afrikanistik-Aegyptologie-Online, 2017)
This paper addresses personal names among the Balant, a community shared between Senegal and Guinea-Bissau. It investigates giving names as an important aspect in Balant society. These names are not mere arbitrary labels. They have socio-cultural functions that depend on various contexts and include family names, honorific names, and birth names (toponyms, temporonyms, survival names, epical names, portrayal names).